Mechanical character of lower limb for table tennis cross step maneuver - Shao, S.; Yu, C.; Song, Y.; Baker, J. S.; Ugbolue, U. C.; Lanzoni, I. M.; Gu, Y. (International Journal of Sports Science & Coaching, 2020)
The agile footwork is a basic but important skill, how to efficiently grasp and improve its performance has always interested coaches and athletes, beginners particularly. The purpose of this study was to investigate the differences in kinetics and kinematics of the cross step between professional athletes and novice athletes using the Oxford foot model. Twenty-two male participants (professional athletes, 11; novice athletes, 11) with dominant right feet participated in the table tennis cross step test. A Vicon motion analysis system and a Novel Pedar insole plantar pressure measurement system were used to record kinematic and kinetic data, respectively. Professional athletes showed significantly smaller forefoot plantarflexion and abduction, but larger hallux dorsiflexion at the cross step ending. In addition, they also showed significantly larger forefoot dorsiflexion and adduction but smaller forefoot eversion as well as rearfoot inversion than novice athletes at the forward-end of the step. In the entire motion, professional athletes performed significantly smaller joints range of motion, especially the hindfoot with respect to tibia angles. Concerning plantar relative load, professional athletes were significantly greater than that of novice athletes in the other toes, lateral forefoot and rear foot. Professional athletes possessed higher footwork agility and greater foot motor technique. The findings on the internal mechanisms of the cross step could help coaches and novice athletes understand the mechanical efficiencies in stroke finishing leading to improvements in performance.